Neck circumference as a predictor of metabolic syndrome: A cross-sectional study. Issue 3 (June 2020) - Laohabut, Issarayus; Udol, Kamol; Phisalprapa, Pochamana; Srivanichakorn, Weerachai; Chaisathaphol, Thanet; Washirasaksiri, Chaiwat; Sitasuwan, Tullaya; Chouriyagune, Charoen; Auesomwang, Chonticha
Highlights: Neck circumference (NC) is a tool for predicting metabolic syndrome (MetS). NC ≥38 in men and ≥33 in woman is the best value for predicting MetS in Thais. NC is correlated with waist circumference, body mass index, waist-hip/height ratio. NC is significantly associated with cardiometabolic risk factors. Abstract: Background: Data relating to the association between neck circumference (NC) and metabolic syndrome (MetS) in Southeast Asian population are scarce. Aims: We aimed to investigate association between NC and MetS in Thai adults, and to determine gender-specific NC cutoff values for predicting MetS. Methods: This cross-sectional study enrolled patients aged ≥18 years that attended the health examination center at Siriraj Hospital (Bangkok, Thailand) during February 2016 to January 2017. Demographic, clinical, anthropometric data, and biochemical investigations for diagnosing MetS were collected. Results: 390 patients (age 35.5 ± 9.7 years with range 20–73 years; 81.3% women) were included. Mean NC was significantly higher in MetS than in non-MetS ( p  < 0.001). Receiver operating characteristic curve analysis revealed NC ≥38 cm and ≥33 cm to be the optimal cutoff points for MetS in men and women, respectively. Body mass index and anthropometric indices were positively correlated with NC in both men and women. Among women, all components of MetS were significantly associated with NC. Conclusions: Using the identified gender-specific cutoff values, NC is a useful tool for predicting MetS in Thais. NC was found to be well-correlated with almost all of the metabolic risk factors, anthropometric indices, and MetS components evaluated in this study.